PENGGUNAAN MODEL KOOPERATIF TEKNIK MAKE A MATCH DALAM PENINGKATAN PEMBELAJARAN BAHASA INGGRIS PADA SISWA KELAS IV - WIRANTO, RETSADA ADE (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The use of Model Cooperative Engineering Make A Match In Improved Student Learning English In IV Grade. The purpose of this research is to improve students' English learning fourth grade with the use of cooperative learning techniques make a match. This study was conducted in three cycles. Each cycle consists of the planning, execution, observation, and reflection. The subjects were fourth grade students. Data sources of this study are students, researchers, and observer. Data was collected with tests and non-test techniques. The validity of the data using triangulation techniques and triangulation of data sources. Conclusion of research is the use of cooperative learning techniques make a match can improve students learning English in fourth grade. Keywords: Make A Match technique, improvement of learning English Abstrak: Penggunaan Model Kooperatif Teknik Make A Match Dalam Peningkatan Pembelajaran Bahasa Inggris Pada Siswa Kelas IV. Tujuan penelitian ini untuk meningkatkan pembelajaran Bahasa Inggrispada siswa kelas IV menggunakan Model Kooperatif Teknik Make A Match. Penelitian dilaksanakan dalam tiga siklus. Setiap siklus terdiri dari perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian adalah siswa kelas IV. Sumber data penelitian adalah siswa, peneliti, dan observer. Teknik pengumpulan data menggunakan teknik tes dan non tes. Validitas data menggunakan triangulasi data dan sumber. Simpulan penelitian adalah penggunaan model pembelajaran kooperatif teknik make a matchdapat meningkatkan pembelajaran Bahasa Inggris pada siswa kelas IV. Kata kunci: Teknik Make A Match,Pembelajaran Bahasa Inggris